Mast cell activation test in chlorhexidine allergy: a proof of concept. (December 2020) - Elst, Jessy; van der Poorten, Marie-Line M.; Faber, Margaretha A.; Van Gasse, Athina L.; Garvey, Lene H.; Bridts, Chris H.; De Puysseleyr, Leander P.; Mertens, Christel; Hagendorens, Margo M.; Sabato, Vito; Ebo, Didier G.
Abstract: Background: Immediate drug hypersensitivity reactions are an increasing public health issue and a frequent cause of life-threatening anaphylaxis. Conventional confirmatory testing include skin tests and, for a few drugs, quantification of drug-specific immunoglobulin E (IgE) antibodies. However, none of these tests are absolutely predictive for the clinical outcome, and can yield false-negative and false-positive results. We performed a proof-of-concept study to assess whether a mast cell activation test could improve diagnosis of IgE-mediated chlorhexidine hypersensitivity, a common cause of perioperative anaphylaxis. Methods: Human mast cells were generated from CD34 + progenitor cells and sensitised with patients' sera to become IgE+ human mast cells (dMC IgE+ ), and then incubated with chlorhexidine to assess degranulation. We compared the diagnostic performance of this mast cell activation test with serum from patients with and without positive skin test and basophil activation test to chlorhexidine. Results: In dMC sensitised with sera from patients with a positive skin test and basophil activation test to chlorhexidine showed drug-specific and concentration-dependent degranulation upon stimulation with chlorhexidine, determined by surface upregulation of the degranulation marker CD63. In contrast, dMC sensitised with sera from patients with a negative skin test and basophil activation test to chlorhexidine were unresponsive in the mast cell activation test. Conclusions: Our study suggests that the mast cell activation test can be used to diagnose IgE/FcεRI-dependent immediate drug hypersensitivity reactions. It also shows potential to assess the clinical relevance of drug-specific IgE antibodies in their ability to elicit mast cell degranulation, and therefore discriminate between allergy and sensitisation. Extended studies are required to verify whether this technique can be used in other causes of perioperative anaphylaxis.